Embodied Complexity in Choral Singing - Daniel Galbreath (Airea, 2020)
Amateur musical ensembles draw participants from widely varying disciplines into shared artistic activity in a way that few other artforms do; in particular, choral music, in which bodies both create and directly receive sound, raises profound questions of how performers’ uniquely embodied creative approaches interact. Amateur choral singing therefore offers a lens into how musical creativity is distributed among, and emergent from, a diverse group of individuals. This article explores how the performance of indeterminate and improvisatory choral works offers a powerful example of this distributed creative agency via a network of sounding bodies.